2021
DOI: 10.1155/2021/6568436
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Physical and Dynamic Mechanical Properties of Temperature‐Water Coupled Sandstone

Abstract: In order to study the influence characteristics of water bath at different temperatures on rock physical and dynamic mechanical properties, a total of 15 groups of temperature-water bath treatment were carried out on coal mine roadway sandstone at 25°C∼95°C, and the basic physical parameters were tested. The impact compression test was carried out using the split Hopkinson pressure bar (SHPB) device. The results show that, with the increase of water bath temperature, the particle gap on the specimen surface in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Li et al [2] carried out impact tests on limestone, dolomite, and sandstone. Ping et al [3][4][5][6][7] conducted impact compression tests on different types of sandstone under high-temperature and different HP conditions to study their mechanical properties and analyze their stress balance. Wang et al [8] investigated the variation in the acoustic energy of granite under combined dynamic and static loading; they found that the law of acoustic emission energy presents two distinct characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [2] carried out impact tests on limestone, dolomite, and sandstone. Ping et al [3][4][5][6][7] conducted impact compression tests on different types of sandstone under high-temperature and different HP conditions to study their mechanical properties and analyze their stress balance. Wang et al [8] investigated the variation in the acoustic energy of granite under combined dynamic and static loading; they found that the law of acoustic emission energy presents two distinct characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al [29] analyzed the mechanical properties of sandstone under the joint coupling of temperature, stress, and water but only performed static tests. Ping et al [30] only studied the dynamic properties of sandstone under temperature-water coupling but did not perform relevant tests on the sandstone under a combination of dynamic and static loading.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the strain rate and granite's dynamic compressive strength have a favorable correlation at high temperatures. Ping et al [16] analyzed the sandstone's mechanical properties under different loading rates and six temperature conditions (25,200,400, 600, 800, 1000 • C). The correlation between dynamic peak stress and peak strain and loading rate is positively correlated under the same temperature conditions, while the correlation between dynamic elastic modulus and temperature is opposite.…”
Section: Introductionmentioning
confidence: 99%